"It Feels Different": A Qualitative Study of Schizophrenic Client Couples About Sexuality - Meyke Rosdiana; Fandro Armando Tasijawa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
One of the basic needs of human life is sexuality. Sexuality in schizophrenic clients has not been explored optimally by researchers and health workers in hospitals or health centers. Various previous studies have explored antipsychotic drugs that cause sexual dysfunction. However, the experience of intimacy and sexual relations between schizophrenic clients and their partners is not necessary to help maintain relationships that positively impact schizophrenia recovery. The method used in this research is qualitative research with a phenomenological approach. This research was conducted from August to September 2022 at the Outpatient Poly Hospital, Dadi Makassar Hospital. Seven participants were recruited using purposive sampling. Participants were interviewed in depth using a voice recorder, transcribed the data, validated, and analyzed using the Colaizzi method. The results of this study found three themes, namely (1) caring for a partner because of love, (2) "it feels different" during sexual intercourse, and (3) the quality of sexual intercourse decreases due to drugs. New insights in this study about caring for a partner because of love, can inspire others to care for clients with sincerity, sincerity, and complete love regardless of the disease. This study also identifies problems that must be resolved by every health worker to be comprehensive in sexual assessment and intervention for schizophrenic clients and their partners. Abstrak: Salah satu kebutuhan dasar kehidupan manusia adalah seksualitas. Seksualitas pada klien skizofrenia belum dieksplorasi secara maksimal oleh peneliti dan tenaga kesehatan di rumah sakit ataupun puskesmas. Berbagai penelitian sebelumnya telah mengeksplorasi obat antipsikotik yang menyebabkan terjadinya disfungsi seksual. Namun, pengalaman keintimanan dan hubungan seksual klien skizofrenia serta pasangannya belum diteliti untuk membantu menjaga hubungan intim yang berdampak positif bagi recovery skizofrenia. Metode yang digunakan dalam penelitian ini yaitu penelitian kualitatif dengan pendekatan fenomenologi. Penelitian ini dilaksanakan pada bulan Agustus sampai September 2022 di Poli Rawat Jalan rumah sakit Dadi Makassar. Tujuh partisipan direkrut menggunakan purposive sampling. Partisipan diwawancarai mendalam menggunakan voice-recorder, data ditranskripsi, divalidasi, dan dianalisis menggunakan metode Colaizzi. Hasil penelitian ini menemukan tiga tema, yaitu (1) merawat pasangan karena cinta, (2) “rasanya beda” saat berhubungan seksual, (3) kualitas berhubungan seksual menurun karena obat. New insight dalam penelitian ini tentang ‘merawat pasangan karena cinta”, hal ini dapat menginspirasi orang lain dalam proses merawat klien dengan tulus, ikhlas dan cinta yang utuh tanpa melihat penyakitnya. Penelitian ini juga mengidentifikasi masalah yang harus diselesaikan oleh setiap tenaga kesehatan agar komprehensif dalam pengkajian dan intervensi seksual kepada klien skizofrenia dan pasangannya.